LEXICAL ASSIMILATION OF BORROWED WORDS FROM ENGLISH INTO UZBEK LANGUAGE - Nazarova, Gulbahor (Журнал иностранных языков и лингвистики, 2021)
In this article it is claimed that borrowing as means of replenishing the vocabulary of present-day Uzbek is of much greater importance and is comparatively active only in the field of scientific terminology and social-political terminology as many terms are often made up of borrowed morphemes, mostly morphemes from classical languages.